1969
DOI: 10.1037/h0028140
|View full text |Cite
|
Sign up to set email alerts
|

Searching for words in letter sets of varying size.

Abstract: The >S"' s task was to list all the 4-letter words he could make up from a set of 5-10 different letters. Responses occurred rapidly at first and then more slowly as S exhausted his store of words. When S had more letters to work with, he could generate a greater total number of words, but took longer to produce any given fraction of them. Thus with 5 letters, 5 found 80% of his limit of 8 words in less than 5 min., whereas with 10 letters, S took more than 15 min. to find 80% of his limit of 43 words. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Such a model was proposed by Kaplan, Carvellas and Metlay (1969) to account for the performance of people who had been asked to produce as many four-letter words as they could from sets of letters varying in number from five to ten. Indow and Togano (1970) referred to this model as the constant rate and exhaustive scanning (CRES) model, for obvious reasons.…”
Section: Lexical Searchmentioning
confidence: 99%
“…Such a model was proposed by Kaplan, Carvellas and Metlay (1969) to account for the performance of people who had been asked to produce as many four-letter words as they could from sets of letters varying in number from five to ten. Indow and Togano (1970) referred to this model as the constant rate and exhaustive scanning (CRES) model, for obvious reasons.…”
Section: Lexical Searchmentioning
confidence: 99%
“…Thus, subjects who were able to name a larger number of cities approached their higher asymptotes more slowly than did subjects who could name fewer cities. Kaplan, Carvellas, and Metlay (1969) showed that the inverse correlation between N and Adid not arise from individual differences between subjects because it also occurs within individuals exposed to different conditions. In their experiment, each subject was asked to generate as many 4-letter words as possible from a pool of letters ranging from 5 to 10 across conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Asymptotic recall level and rate of approaching asymptote have consistently been found to be inversely related, such that higher levels of asymptotic recall produce a slower approach to asymptote (see, e.g., Bousfield & Sedgewick, 1944;Herrmann & Chaffin, 1976;Herrmann & Murray, 1979;Johnson, Johnson, & Mark, 1951;Kaplan, Carvellas, & Metlay, 1969). However, Burns and Schoff (1998) showed that this relationship is often violated when differing levels of item-specific and relational processing are performed.…”
mentioning
confidence: 96%